(untitled) (Research, Society and Development, 2025)
The treatment of neoplasms is a major medical challenge, and the search for new molecules with antineoplastic potential is essential to advance prevention and treatment options. Vegetables have stood out as promising sources of anticancer compounds, but the concomitant consumption of herbal medicines and conventional medicines can generate dangerous drug interactions. In Brazil, the rich biodiversity and the traditional use of medicinal plants give great importance to herbal medicines, but their effects need to be scientifically proven. Drugs such as vincristine, vinblastine and taxol, derived from plants, are already used in antineoplastic chemotherapy. This work carried out a retrospective bibliographic survey to highlight the antineoplastic potential of plant derivatives, selecting 14 articles published in the last 5 years. The databases used were SciELo, PubMed, Google Scholar and CAPES Periodicals. Articles from national and international authors were researched on the use of plant derivatives with antineoplastic potential. Natural products such as triterpenoids, curcumin, isothiocyanates and sulforaphane have demonstrated anticancer activity, modulating the cell cycle and inducing apoptosis. However, limitations such as low bioavailability and instability hinder its therapeutic application. Curcumin, for example, faces challenges due to its physicochemical properties. Curcumin, for example, faces challenges due to its physicochemical properties. Despite promising evidence, more research and randomized clinical trials are needed to ensure the efficacy, safety, and understanding of drug interactions of these compounds in cancer treatment.